Correction: Remote meta C–H bond functionalization of 2-phenethylsulphonic acid and 3-phenylpropanoic acid derivatives. Issue 2 (8th December 2016) - Modak, Atanu; Mondal, Anirban; Watile, Rahul; Mukherjee, Semanti; Maiti, Debabrata
Abstract : Correction for 'Remote meta C–H bond functionalization of 2-phenethylsulphonic acid and 3-phenylpropanoic acid derivatives' by Atanu Modak et al., Chem. Commun., 2016, 52, 13916–13919.